Quantitative Analysis of Heavy Metals and Organic Compounds in Soil from Deir Kanoun Ras El Ain Dump, Lebanon - Jamilah Borjac; Manal El Joumaa; Lobna Youssef; Rawan Kawach; Diane A. Blake (The Scientific World Journal)
Recently, there has been a worldwide concern regarding soil contamination by heavy metals and organic compounds, especially in the developing countries including Lebanon that has suffered from solid waste mismanagement for decades. Deir Kanoun Ras El Ain is a village in southern Lebanon that possesses one of the country’s worst dumps, and its leachates influx into a running canal that irrigates surrounding agricultural lands. The aim of this study was to determine the levels of some toxic heavy metals and organic compounds in different soil samples collected from the dump and along the canal during winter and summer seasons. Six research sites (four from the dump and two along the canal) were selected, and the soil samples for analysis were collected from a depth of around 10 cm. Heavy metals (lead, cadmium, arsenic, and mercury) and organic compounds (phthalates, bisphenol A, and polyaromatic hydrocarbons) content were determined using atomic absorption and high pressure liquid chromatography, respectively. The conducted research confirmed high levels of contamination in the collected soil samples by both heavy metals and organic compounds. The present study provided evidence that different sampling sites accumulated heavy metals at concentrations that exceeded the average maximum permissible levels for sewage sludge and agricultural land. These findings suggest the need for mitigation measures by the Lebanese authorities and new waste management programs to resolve the problems associated with uncontrolled dumping of solid wastes in Lebanon.